Exploring the drivers of firm value in the transportation and logistics industry - Lautania, Maya Febrianty; Marpaung , Aura Maghfira; Nuraini A, Nuraini A; Ikhsan , Adhisyahfitri Evalina (Journal of Contemporary Accounting, 2026)
This study explores the drivers of firm value in the transportation and logistics industry by examining the influence of capital structure, institutional ownership, and profitability. The research focuses on companies listed on the Indonesia Stock Exchange during 2021–2023 and applies a quantitative approach using secondary data from annual financial reports. Firm value is measured by Tobin’s Q, capital structure by the Debt to Asset Ratio (DAR), institutional ownership by the proportion of institutional shareholding, and profitability by Return on Equity (ROE). Multiple linear regression is employed as the analytical technique. The findings indicate that capital structure and profitability have a positive effect on firm value, suggesting that well-managed leverage and higher profitability strengthen investor confidence in firm performance. Conversely, institutional ownership does not show a significant effect, implying that a larger proportion of institutional shares does not necessarily enhance firm value. These results emphasize the role of financial management and profitability in shaping firm value within the transportation and logistics industry.